EFFECT OF HUMIC ACID LEVELS AND BIOSTIMULANT TREATMENTS ON GROWTH, YIELD, AND VOLATILE OIL PRODUCTION OF CORIANDER (Coriandrum sativum L.) - Rabeeah Altarhouni; Abobaker Alsanose; Aisha Abudabbus; Muhannad Alwoshesh; Abd El-Rahman Abd El-Rahman (Mesopotamia Journal of Agriculture)
A study was done during two consecutive seasons of 2022/2023 and 2023/2024 to study the effects of humic acid (HU 4, 8, and 12 kg/hectare) as the main plot and BM (Azotobacter chrococum, Azospirulm Brasiliense, and Bacillus polymaxa) and algae extracts (ALG) as the subplot as well as their interactions on plant growth. The design of the experiment was a split plot, including 16 treatments and three replicates. The results showed that the growth parameters, fruit yield measurement, and oil production were noticeably enhanced using humic acid and biostimulants (BM and ALG). In this concern, the high-rise values were obtained by utilizing the high level of HU (12 kg/hectare) with bio-fertilizer (BM + ALG) application compared with control during both seasons. Also, GCMS analysis of the volatile oil revealed that HU and a mixture of bacteria and algae extract had improved the primary volatile oil components of coriander (Linalool - α-Pinene - γ-Terpinene - P-Cymene - Geranial Acetate).